Fluorinated small molecule derivatives in cancer immunotherapy: emerging frontiers and therapeutic potential - Leong, Ka Fai; Chen, Zihan; Coghi, Paolo (Frontiers in Immunology, 2025)
Immunotherapy has revolutionized cancer treatment by leveraging the body’s immune system to recognize and eliminate tumor cells. While monoclonal antibodies and checkpoint inhibitors have shown dramatic clinical successes, small molecules are increasingly recognized for their potential to modulate the immune system with improved pharmacokinetics and oral bioavailability. The incorporation of fluorine atoms into small molecule structures has become a widely used strategy to enhance therapeutic efficacy. Fluorine’s unique chemical properties such as high electronegativity, metabolic stability, and ability to modulate lipophilicity make fluorinated small molecules especially attractive for immunotherapeutic applications. This minireview highlights recent advances in fluorinated small molecules that target key immune pathways, including immune checkpoints, STING agonists, IDO inhibitors, and kinase pathways involved in immune regulation. We explore the chemical rationale, mechanisms of action, and therapeutic outcomes of fluorinated compounds currently in preclinical and clinical development. The discussion also addresses challenges such as immunotoxicity, resistance, and design strategies to overcome them. Together, these findings underscore the growing relevance of fluorinated small molecule immunotherapeutics in cancer treatment.